NIBRS Data Available for Secondary Analysis - Dunn, Christopher S. (Journal of quantitative criminology, 1999)
The NIBRS data program currently being implemented by the FBI and local lawenforcement agencies has by now produced sufficient data for archiving anddistribution. Although not representative of crime in the United States, existing NIBRS data can be used to investigate the nature of crimesknown to the police compared to the traditional UCR data. The Bureau ofJustice Statistics has requested the National Archive of Criminal JusticeData to store and make NIBRS data available to interested users. The datafrom 1996 will shortly be available from the NACJD web site. The 1996 datacontain almost 6.5 million records and the FBI's full file includes about 361 Mbytes of data. The data have been disaggregated from the FBI's complex single file into 11 segment levels or record types. This makes theindividual record types easier and faster to analyze than using the fullfile, which more closely resembles a relational database than a hierarchicalfile. However, splitting apart the record types requires that specialprocedures be used to merge files of different record types, which would benecessary if a user were interested in analyzing variables appearing in morethan one record type (e.g., comparing offender and victim ages). These procedures are described, and a test comparing the time to run a simple frequencycount using the full file against the merged files shows that using themerged files is considerably more efficient. Also discussed are some futuredevelopments to facilitate the analysis of NIBRS data.